THE EFFECT OF HIGH INTENSITY INTERVAL TRAINING AND FARTLEK TRAINING ON INCREASING VO2MAX TOKAMBANG FUTSAL CLUB - Andi Ridwan; Muh. Syahrul Saleh; La Kamadi (ILIN Education Indonesia, 2023)
The purpose of this study was to improve the Vo2Max of Tokambang FC futsal players. This type of research uses experimental research which is carried out for 16 meetings with the treatment of high intensity interval training and fartlek training which is carried out through a training program that has been prepared. This study aims to determine: (1) whether there is an effect of interval training to increase Vo2Max; (2) whether there is an effect of fartlek training to increase Vo2Max; (3) whether there is a difference between high intensity interval training and fartlek This research was conducted using an experimental method with a Two-group pretest-posttest design. pmain Tokambang futsal club The sampling technique was matched pair. The research instrument used Multi stage fitness. The data analysis technique used in this study is t-test to determine the comparison of high intensity and fartlek exercises in increasing Vo2Max. Based on the results of the study are as follows. (1) There is an effect of increasing Vo2Max in PS futsal athletes. Himalaya with interval training, which is evident from the t value (13.321) > t table (2.132). (2) There is an effect of increasing Vo2Max in PS futsal athletes. Himalaya with fartlek training, which is evident from the t value (10.994) > t table (2.132). (3) High intesnity interval training and fartlek training are equally good at increasing VO2max in Tokambang futsal club players because there is no significant difference in results, which is evident from the value of t count (0.587) > t table (2.201).